2011
DOI: 10.1093/hmg/ddr224
|View full text |Cite
|
Sign up to set email alerts
|

Methylation screening of reciprocal genome-wide UPDs identifies novel human-specific imprinted genes†

Abstract: Nuclear transfer experiments undertaken in the mid-80's revealed that both maternal and paternal genomes are necessary for normal development. This is due to genomic imprinting, an epigenetic mechanism that results in parent-of-origin monoallelic expression of genes regulated by germline-derived allelic methylation. To date, ∼100 imprinted transcripts have been identified in mouse, with approximately two-thirds showing conservation in humans. It is currently unknown how many imprinted genes are present in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 54 publications
4
60
0
1
Order By: Relevance
“…To explain this finding, Buiting et al [144] proposed a model in which the binding of a transcriptional complex in the unmethylated 2B-promoter region (paternal) blocks the transcriptional complex that regulates the expression of an alternate transcript from the promoter located upstream to exon 1, resulting in a low abundance of the paternal allele. Recently, Nakabayashi et al [145] confirmed the maternal methylation of the RB1 DMR in a study of rare reciprocal genome-wide uniparental disomy samples in patients with Beckwith-Wiedemann and SilverRussell syndrome-like phenotypes.…”
Section: Predict Imprinted Genes and Bladder Cancermentioning
confidence: 93%
“…To explain this finding, Buiting et al [144] proposed a model in which the binding of a transcriptional complex in the unmethylated 2B-promoter region (paternal) blocks the transcriptional complex that regulates the expression of an alternate transcript from the promoter located upstream to exon 1, resulting in a low abundance of the paternal allele. Recently, Nakabayashi et al [145] confirmed the maternal methylation of the RB1 DMR in a study of rare reciprocal genome-wide uniparental disomy samples in patients with Beckwith-Wiedemann and SilverRussell syndrome-like phenotypes.…”
Section: Predict Imprinted Genes and Bladder Cancermentioning
confidence: 93%
“…The remaining 27 genes were considered the top candidates for novel IGs from the present work (Table 1). Candidate locus with one probe with maternal methylation exclusively in placenta (HM27K) [13] a Provisional imprinted gene described in the Catalogue of Imprinted Genes and Parent-of-Origin Effects in Humans and Animals. …”
Section: Mining Novel Candidate Imprinted Genes Using the Hm450k Methmentioning
confidence: 99%
“…In general, the approaches used to identify novel IGs are based on three main features: presence of an epigenetic signature, monoallelic expression dependent on parental origin, and specific characteristics of the DNA sequence (such as Short interspersed nuclear elements-SINE-exclusion) [3]. Currently, large-scale transcriptome and methylome analyses of data obtained by high-throughput technologies, such as microarrays and next-generation sequencing, are enabling the identification of new candidate IGs [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Parent-of-origin-specific methylation of CpG85 has been confirmed by other studies. [15][16][17][18] At present, nearly 100 imprinted human genes have been identified, and several studies have taken a genome-wide look at parent-of-origin-specific DNA methylation in order to identify novel imprinted genes. 18,19 Retrocopies are instructive genomic elements for studying the evolutionary dynamics and constraints of DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] At present, nearly 100 imprinted human genes have been identified, and several studies have taken a genome-wide look at parent-of-origin-specific DNA methylation in order to identify novel imprinted genes. 18,19 Retrocopies are instructive genomic elements for studying the evolutionary dynamics and constraints of DNA methylation. Based on a whole genome methylome data set with single base pair (bp) resolution, we have investigated the methylation status of all human CGIs associated with a retrocopy and of their genomic environment, which we defined as the region 1,000 bp up-and down-stream of a retrocopy.…”
Section: Introductionmentioning
confidence: 99%